Definitions, indications and practice of urotherapy in children and adolescents: - A standardization document of the International Children's Continence Society (ICCS). Issue 2 (April 2021) - Nieuwhof-Leppink, A.J.; Hussong, J.; Chase, J.; Larsson, J.; Renson, C.; Hoebeke, P.; Yang, S.; von Gontard, A.
Summary: Background: Urotherapy is an umbrella term for all non-surgical, non-pharmacological interventions for lower urinary tract disorders (LUTD) in children and adolescents. Urotherapy is a specialized practice, which has become mainstay therapy not only for daytime urinary incontinence, but also for nocturnal enuresis, functional constipation and fecal incontinence. The aim of urotherapy is to achieve the normalization of the micturition and bowel pattern and to prevent further functional disturbances by repeated training. It is well known that in the treatment of adult and childhood incontinence a team approach is best, where there are shared areas of expertise and also discipline-specific expertise available. Aim: We present a consensus view from a cross-professional team of experts affiliated with the International Children's Continence Society on definitions, indications and practice of urotherapy. This is a selective, non-systematic review with practical recommendations for the implementation and research on urotherapy. Methods: The document uses the globally accepted ICCS terminology. Evidence-based literature serves as the basis, but in areas lacking in primary evidence, expert consensus is used. Before submission, a full draft was made available to all ICCS members for additional comments. Results: Urotherapy uses non-pharmacological, non-surgical methods and focuses on behavioral interventions, largely based on cognitive-behavioral psychotherapy (CBT). Standard urotherapy comprises components such as provision of information, instructions, life-style advice, counselling and registration of symptoms. Specific urotherapy is tailored towards specific disorders and includes alarm treatment, biofeedback training, pelvic floor training, neurostimulation and other interventions. Fig. 1. Urotherapy is a treatment that addresses all aspects of incontinence, leading to the best clinical outcome. This includes somatic, psychosocial, and behavioral problems and quality of life. Therefore urotherapy is recommended by the ICCS as the first-line treatment for most types of LUTD. The document is intended to be clinically useful in primary, secondary and tertiary care. Summary Figure 1 Daytime urinary incontinence and enuresis. Summary Figure 1